Software patterns catalog based on a new classification scheme. (25th November 2011) - Hasso, Sargon; Carlson, R.C.; Fayad, Mohamed E.; Singh, Shivanshu K.
SUMMARY There are many software pattern catalogs that exist in the published literature today, but none of them uses a consistent classification technique that results in evolving and extensible pattern catalog. We have created a new classification scheme and used it as the basis for constructing a software pattern catalog. It is a uniform approach for creating, maintaining, and expanding the catalog. We present a brief overview of the classification scheme, describe the resulting catalog and the principles underlying its construction, show how to use the catalog, and demonstrate some of its benefits for software designers. Copyright © 2011 John Wiley & Sons, Ltd.